If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6n + -33 = 3n Reorder the terms: -33 + 6n = 3n Solving -33 + 6n = 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. -33 + 6n + -3n = 3n + -3n Combine like terms: 6n + -3n = 3n -33 + 3n = 3n + -3n Combine like terms: 3n + -3n = 0 -33 + 3n = 0 Add '33' to each side of the equation. -33 + 33 + 3n = 0 + 33 Combine like terms: -33 + 33 = 0 0 + 3n = 0 + 33 3n = 0 + 33 Combine like terms: 0 + 33 = 33 3n = 33 Divide each side by '3'. n = 11 Simplifying n = 11
| [2+(3*2)]= | | -1=-s | | 6+17y=-15y+14y | | -15x^2+29x-12=0 | | 8x-7=2(2x+7)-5 | | 4=u-6 | | 25x^2-215x+280=0 | | 2[5+2(6+3*4)]= | | x^4+5x^2-4x^2-20x=0 | | G+1=-1 | | Ln(3x-4)=5 | | 15+g=16 | | 10m-22=58 | | 3(x-6)-9=-3(-8x+7)-5x | | 5x+4-7x=5x-13 | | G-1=7 | | -9x+2=-3(3x+2) | | -26=6(v-6)-8v | | x/4+10=-2 | | 12=y+4 | | 6x-4=2x+28 | | 3xsquared-150x-1200=600 | | -13.00x+2.00=8 | | E+6-1=3 | | 2.3=4.5X+30.2 | | -13.00+2.00=8 | | y=15x+27 | | 0.05-0.6x=5.3 | | (2ax+bx)(2ax+bx)= | | R-3.5=-2.1 | | 15=5+y | | 32x^3+13x^3+23x^4= |